(3EHOGY MceI GdMcje aj HjGf HSe Gddg GdQMef GdQMjes - (3CHh SYjO eMeO GdNGOejs
(3BNQgG (B:s
(3SHMGf QHfG QH GdYRI YeG jUahf hSdGe Ydi GdeQSdjf hGdMeO ddg QH GdYGdejf s
(3Vef eLehY s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa YGeI (B- (3U (B94 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3eLGejY (B608) s
(3JHUQI GdJQGLe(Bs
Keywords: (3GdeYGQa GdYGeIs